P5_5 Boiling the Ocean - Irwin, Benedict; Hicks, Peter; Lerman, Hannah (Physics Special Topics, 2013)
We approximate the energy required to boil the entire of the Earth’s oceans as which make up the majority of the water on Earth. The energy is calculated to be 5.33x10^26 Joules. We then put into perspective how much energy this is in the form of nuclear weapons, meteorite impacts, mass-energy conversion and 9V household batteries.